RADIOGRAFIC ASSESTMENT AND JOINT DAMAGE IN EARLY RHEUMATHOID ARTHRITIS PATIENTS TREATS WITH METHOTREXATE - Spasovski, Dejan; Sandevska, Emilija; Pivkova-Veljanovska, Aleksandra; Balkanov, Svetlana Krstevska (Journal of Morphological Sciences, 2021)
In rheumatoid arthritis (RA), progression of the radiographic damage of hand and feet joints is a significant and objective variable for evaluation of disease activity as well as measurement of treatment outcome . The aim of this study was to evaluate the RA activity with radiographic evaluation of hand joints in patients with early RA treated with Methotrexate by using acute phase reactants, as rheumathoid factor (RF), C-reactive protein (CRP) and DAS28 index of disease activity. We tested 70 participants (35 control patients, 35 untreated RA patients). Patients were treated with Methotrexate at an average dose of 10 mg once weekly. For clinical evaluation of disease activity radiographic index (RI), sedimentation, CRP and RF in certain time intervals (0-time, after 6, 9 and 12 months) were analyzed in every patient. RI showed an increased radiographic progression of hand joint damage in time intervals between 0-time and 9 months (p=0,0167) and between 0-time and 12 months (p=0.0089). The statistical analysis showed statistically significant differences among mean values of ESR in the four-time intervals (p=0.00002). Keywords: rheumatoid factor, acute phase reactants, rheumatoid arthritis https://doi.org/10.55302/JMS2142026s